The Key Factor - Structural Equation Models for Success in Souphanouvong University Graduates’ Career - VANG, Khammee; ANOLAC, Vira; THAVONESACK, Thipphakone; PHAIGNAVONG, Somechay; CHITTAVONE, Chanthalack; PHOUNNALY, Phayvanh; Lattananongsy, Sengmany (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purposes of this research were to study: An assessment of the graduates’ employability from 2015-2020 after graduation from Souphanouvong University The sample groups were 220 alumni, who completed their studies between the year 2015-2020 at Souphanouvong University, divided into 8 northern provinces and Vientiane Capital. The stratified sampling technique was applied for selecting the samples. The key instruments, used to collect data, was a questionnaire with multiple choices in 5-point Likert scales. The statistics used in the data analysis was frequency, percentage, mean and standard deviation. The research results were below: Alumni who graduated from Soupahnovuong University are looking for jobs after graduation, and overall, the work they are assigned or offered is related to the subjects and degrees they have completed, with a score mean at 4.07, with a standard deviation (SD) at 1.012 and 70.8% of employers informed that they were employing graduates at the level of their degree. Most of them work in technical positions and 83.6% of respondents are still employed in their first job and 14.5% did not continue employment the first job. Among those who have changed their job, most of them did it for a better paid job (37.5%) and 77.8% of respondents are currently employed. The role of social network (friends/relative/teacher/other) was the main path to find the first job. The role of the state is still extremely important to recruit new graduates to secure and stable positions, Working for employers must use foreign languages at work, which accounts for 81.9%. Different languages which are primarily used in work are English, Thai, Vietnamese and Chinese, but 79.2% of them think the language level of the graduates is too low. The issue of equality in job search by sex and ethnicity can be summarized as follows: Women and men have equal access to employment with a statistically significant period of 0.05 with a statistical value in the test. Hypothesis: Chi-Square = 0.200, D.F. = 1, Sig. of Chi-Square = 0.655 and the lower Lao and other ethnic groups had equal access to employment with a statistically significant range of 0.05. With statistical values ​​in the hypothesis test: Chi-Square = 2.61, D.F. = 5, Sig. of Chi-Square = 0.755. Most of the employers desire Souphanouvong University to provide and teach students with problem-solving skills, followed by foreign language skills, and having proficiency in Lao language skills.